BLESSINGS FOR CHILDREN (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article discusses the meanings and types of blessings for the sons of Kyrgyz people is widely used in the daily life of the Kyrgyz people. There is a belief in the power of words and an influence of blessings in achieving goals. The examples of the blessings are given in the article. The Kyrgyz people believe in blessings; a blessing positively influences a person’s mood and state of mind, which leads only to kindness. The following blessings are dedicated to male children: the blessings at the birth of a child, at giving the names to a newly born male child, at circumcision, and when a male child marries. Blessings have a deep meaning that has a great influence on the growth and education of a person.
Keywords: blessing,to bless, praise, kindness, Almighty, universe, procreation, baby